Quality quandaries: Statistical detective work to understand the isotopic ratios in Drum 68660 and the radioactive release at WIPP. Issue Volume 29:Issues 4(2017) (2nd October 2017) - Kelly, E. J.; Weaver, B. P.; Veirs, D. K.
KEY POINT: An incident at the Department of Energy's Waste Isolation Pilot Plant (WIPP) in 2014 resulted in the release of radioactive material into the environment. Initially, it was known that at least one drum in WIPP, identified as drum 68660, was involved. However, questions remained. Could the air-monitor isotopic ratios measured in WIPP at the time of the release be explained by materials in drum 68660 or were other drums involved? Could internal conditions in drum 68660 have caused the breach? What were the implications for 68660's sister drum? These questions needed to be answered as quickly as possible. This analysis, which was completed in three weeks, combined combinatorics and uncertainty analysis to provide scientists with the timely evidence they needed to either answer these important questions or to design experiments to answer them.